The Expansion of E-learning in the UAE: Implications and Opportunities in the Post-COVID-19 Era (Comparative & International Education Series, 2021)
The COVID-19 pandemic has forced higher education institutions (HEI) in the United Arab Emirates (UAE) and globally to hastily rework their systems and become more innovative in their online teaching and learning approach. This chapter presents the conceptual basis for understanding, analyzing, and designing an informed implementation plan for new e-learning systems in the UAE. Rogers' (2003) Diffusion Innovation Theory is used to assess which factors affect the UAE’s public higher education institutions’ intention and ability to adopt e-learning during the COVID-19 era. It is determined, to lower complexities the pandemic presents and promote the UAE’s post-crisis growth, public HEI must rework their traditional higher education model while safeguarding the UAE’s social and cultural standards for e-learning. Overall, with the observed benefits of increased access and developing a new generation of technologically skilled creative thinkers, the UAE’s advanced infrastructure is equipped and ready to become a global hub for e-learning.